KESEDIAAN SUAMI MENGERJAKAN PEKERJAAN RUMAH TANGGA SELAMA ISTRI HAMIL DI KELURAHAN SAMBUNG JAWA KECAMATAN MAMAJANG KOTA MAKASSAR - I MADE SUKARTA; ANDI ZULFAIDAWATY (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Pregnant women experience changes in their body systems, both hormonally and other body systems. This is due to the presence of a fetus in the womb. This condition is added. Fatigue during pregnancy has a negative impact on the mother and the fetus in the womb. Therefore, it needs to be reduced with the help of the husband taking over this role during pregnancy. With the hope that the mother can rest, and take good care of herself. So that pregnancy and delivery are normal. This study aims to find out how the relationship between husband's characteristics and willingness to take up household work during pregnancy and childbirth in Connect Jawa Village, Mamajang District, Makassar City. This type of research is an observational analytic cross sectional approach. The time period is March to September 2021. The total sample size is 49 simple. The results obtained that there is no relationship between education and willingness to take over domestic roles while the variables of employment and income are related. Suggestions as a solution from these findings, although there is no relationship between education and readiness to help in the domestic sphere, it is still necessary to socialize harmonious gender roles. Non-formal and formal workers still always provide time to help their wives work other than those that are natural. ABSTRAKIbu hamil penngalami perubahan sistem tubuhnya baik secara hormonal maupun sistem tubuh lainnya. Hal itu disebabkan karena adanya janin dalam kandungan. Kondisi tersebut ditambah lagiKelelahan selama masa kehamilan berdampak buruk terhadap ibu dan janin yang dikanadung Oleh sebab itu perlu dikurangi dengan bantuan suami mengambil alih peran tersebut selama masa kehamilan. Dengan harapan ibu bisa istirahat, dan merawat diri dengan baik. Sehingga kehamilan dan pesalinan bejalan normal. Penelitian ini bertujuan mengetahui bagaimana hubungan karakteristik suami terhadap kesediaan pengambilan pekerjaan rumah tangga selama hamil dan persalinan di kelurahan Sambung Jawa Kecamatan Mamajang Kota Makassar. Jenis penelitian analitik observasional pendekatan cross sectional. Waktu periode Maret sd September 2021. Besar sample 49 total simple. Hasil diperoleh tidak ada hubungan antara pendidikan dengan kesediaan pengambil alihan peran domestic sementara variable pekerjaan dan penghasilan berhubungan. Saran sebagai solusi dari hasil temuan ini walaupun tidak ada hubungan antara pendidikan dengan kesiapan membantu di ranah domestic namun tetap diperlukan sosialisasi peran gender yang harmonis. pekerja non formal maupun formal tetap selalu menyediaakan waktu untuk membantu pekerjan istri selain yang bersifat kodrat .